2022
DOI: 10.1007/s00535-022-01849-9
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence (AI) models for the ultrasonographic diagnosis of liver tumors and comparison of diagnostic accuracies between AI and human experts

Abstract: Background Ultrasonography (US) is widely used for the diagnosis of liver tumors. However, the accuracy of the diagnosis largely depends on the visual perception of humans. Hence, we aimed to construct artificial intelligence (AI) models for the diagnosis of liver tumors in US. Methods We constructed three AI models based on still B-mode images: model-1 using 24,675 images, model-2 using 57,145 images, and model-3 using 70,950 images. A convolutional neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…With help of a huge sample of FLLs, the model based on the DL method in their study is able to do multi-grouping tasks, and diagnosis performance for every subtype was achievable. The overall accuracy of 89.1% for four discrimination was achieved (33).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…With help of a huge sample of FLLs, the model based on the DL method in their study is able to do multi-grouping tasks, and diagnosis performance for every subtype was achievable. The overall accuracy of 89.1% for four discrimination was achieved (33).…”
Section: Discussionmentioning
confidence: 89%
“…In the testing cohort, both studies showed moderate AUC for each model (0.728-0.775), considering that as each diagnosis process goes through two to three tandem models, the accuracy for differential diagnosis of subtypes might not be ideal. A multicenter study used over 150,000 images focused on the differentiation of FLL subtypes, including cyst, hemangioma, HCC, and liver metastasis (33). With help of a huge sample of FLLs, the model based on the DL method in their study is able to do multi-grouping tasks, and diagnosis performance for every subtype was achievable.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, most studies had focused on the liver, with AI improving the accuracy of an experienced observer, classifying benign from malignant solid liver lesions. 17,18 In addition, DL radiomics of elastography data showed similar diagnostic efficacy with liver biopsy for assessing cirrhosis and advanced fibrosis, 19 potentially eliminating the need for invasive testing.…”
Section: Commentariesmentioning
confidence: 93%
“…83.6%). In addition, the estimation probability of AI for correct diagnosis increases with an increase in the amount of training data, indicating that a highly reliable estimation can be acquired after an increase in training data [51].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…A variety of AI models for diagnosis of liver disease have been reported; some of them reportedly outperform human experts based on their performance. However, the value of the output from AI could be more informative for beginners and non-experts because AI generally shows much higher performance than beginners and non-experts, compared to the experts, especially in the field of imaging diagnosis [42,51]. Another study indicate that the AI for diagnosing focal liver lesions in B-mode US shows the potential to assist less-experienced radiologists in improving their performance and lowering their dependence on sectional imaging in liver cancer diagnosis [41], although the final responsibility for medical decision is on the medical staff.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%